Lentera Sahabat: Program for Peer Facilitator to Prevent Bullying - Pratama, Moch Johan (Utan Kayu Publishing, 2023)
After the study conducted by Olweus (1991) more than two decades ago, interest in bullying topic significantly increased and provides sturdy evidence that Bullying consists among children and adolescents. The result of the introductory survey found that 54% out of 739 high school students in Yogyakarta reported that bullying occurs in their school at last one year and 13% reported that they have been bullied. This current study develops a program called Lentera Sahabat. This program aims to increase high school students' knowledge about bullying and their skills to guide role-play sessions with bullying themes. An untreated Control Group Design with a Dependent Pre-test and Posttest Sample was used as the design. Quantitative data analysis was conducted through mixed design ANOVA statistical test. The results of this study are the increase of student knowledge about bullying and also their skills to guide role-play sessions with bullying themes. Abstrak: Sejak studi yang dilakukan Olweus (1991) lebih dari dua dekade yang lalu, perhatian pada bullying semakin meningkat tajam dan menghasilkan bukti-bukti kuat, bahwa bullying banyak terjadi pada anak dan remaja. Studi pendahuluan penelitian pada 739 siswa dari 10 SMAN Kota Yogyakarta menunjukkan bahwa 54% siswa pernah melihat perilaku bullying di lingkungan sekolah dalam kurun waktu satu tahun terakhir dan 13% siswa mengaku telah menjadi korban bullying. Penelitian ini mengembangkan Program Lentera Sahabat yang bertujuan untuk memberikan pengetahuan tentang bullying dan mengajarkan keterampilan memandu sesi bermain peran dengan tema bullying kepada siswa SMA. Desain yang digunakan adalah Untreated Control Group Design with Dependent Pre-test and Posttest Sample. Analisis data kuantitatif dilakukan melalui uji statistik mixed design ANOVA. Hasil penelitian ini adalah meningkatnya pengetahuan tentang bullying serta keterampilan siswa untuk memandu sesi bermain perandengan tema bullying.